Nitrogen Contribution of Paraserianthes Falcataria Tree Biomass to Corn (Zea Mays. L) Production - Chintu, Richard (2002)
Tree legumes can be an important nitrogen (N) source for cereals in developing countries where little or no fertilizer is used due to prohibitive costs. P. falcataria biomass as a source of nitrogen for com, was studied in a series of field and controlled experiments using 15N labeling techniques. The aim of the study was to characterize the effect of biomass quality on nitrogen mineralization, and on N recovery from P. falcataria residues by com. It was hypothesized that mixing of residues of varying quality would alter residue (litter) quality and nitrogen mineralization. P. falcataria leaves were mixed with P. falcataria roots (P. falcataria mixture). Residue quality assessment was based on the index; (Polyphenol + Lignin)-to-N content. Litter quality was in the order of; P. falcataria leaves > P. falcataria mixture> P. falcataria roots, nitrogen and carbon (C) mineralization also followed the same sequence (P <0.05), indicating that the potential of residues to increase soil inorganic N depends on their quality. P. falcataria leaves including mixture treatments significantly (P<0.05) mitigated soil acidity while P. falcataria roots alone did not. Thus, there is a potential benefit of residues as 'lime' in cropping systems. Leaves under humid tropical conditions decomposed rapidly causmg an initial transitory increase in soil inorganic N, then substantial N03-N leaching from 30 to 60 days after application. Significant amounts of Ca++, Mg++, and K+ were leached beyond the top 20 e m soil profile only after 60 days. There is need to strategically mix residues of contrasting quality, to regulate N release and reduce leaching while increasing soil inorganic N under field conditions. The potential of the 15N indirect and direct labeling methods to estimate N- cycling from tree residues was similar (P<0.05). Com recovered more N from P. falcataria roots than from P. falcataria leaves. Data on com produced under field conditions indicated that, the use of residues in combination with an inorganic N source, as opposed to the sole use of either of them, seems a more effective management strategy for improving N use efficiency, including mitigating soil acidity.